DEVELOPMENT OF MASS SPORTS AS A BASIS FOR HEALTHY LIFE STYLE OF STUDYING YOUTH - Pogosova, S.N; Tinikashvili, G.S (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
In recent years, the problem of the health and physical development of the younger generation has escalated. This topic is of concern to doctors, psychologists, educators and parents. And this is not accidental, as now there is a sharp deterioration in the health and physical fitness of schoolchildren. In this regard, the article is devoted to the leading aspect of the activities of any educational institution, namely the organization of a health-saving educational environment, aimed at optimizing the educational and cognitive activity of students at the expense of their personal potential. In the process of learning, the formation of the needs and abilities to learn without health is put forward in the educational process, and the learning itself is becoming more individualized and acquiring a creative character. Successful implementation of the tasks of personal and professional self-determination of students in school is a differentiated approach to learning, based on the principles of health-saving pedagogy. Teachers also actively use: gaming technology, modular learning technology, project-based, student-centered, informational, health-saving learning technologies, role-playing and intellectual games, the latest educational programs. Teachers use different methods of introducing, consolidating educational material so that children with visual, audio and kinesthetic systems of the world perception will equally well master the material. But no matter how much attention was paid to promoting healthy lifestyles, most people do not get up for a jog in the morning and do not go skiing. Modern people just do not have enough time for sports or healthy food, they would not be late for study or work.